Beyond the Garden: On the Erotic in the Vision of the Middle English Pearl - Spyra, Piotr (Text Matters: A Journal of Literature, Theory and Culture, 2013)
The Middle English Pearl is known for its mixture of genres, moods and various discourses. The textual journey the readers of the poem embark on is a long and demanding one, leading from elegiac lamentations and the erotic outbursts of courtly love to theological debates and apocalyptic visions. The heterogeneity of the poem has often prompted critics to overlook the continuity of the erotic mode in Pearl which emerges already in the poem’s first stanza. While it is true that throughout the dream vision the language of the text never eroticizes the relationship between the Dreamer and the Pearl Maiden to the extent that it does in the opening lines, the article argues that eroticism actually underlies the entire structure of the vision proper. Taking recourse to Roland Barthes’s distinction between the erotic and the sexual to explain the exact nature of the bond which connects the two characters, the argument posits eroticism as an expression of somatic longing; a careful analysis of Pearl through this prism provides a number of ironic insights into the mutual interactions between the Dreamer and the Maiden and highlights the poignancy of their inability to understand each other. Further conclusions are also drawn from comparing Pearl with a number of Chaucerian dream visions. Tracing the erotic in both its overt and covert forms and following its transformations in the course of the narrative, the article outlines the poet’s creative use of the mechanics of the dream vision, an increasingly popular genre in the period when the poem was written.